Household Chemical Exposure and Infertility in Reproductive Age Couples Living in Agricultural Regions of Yogyakarta - Kurniawati, Erna Yovi; Rizkiana, Erin (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background : Exposure to household chemicals, especially those containing endocrine-disrupting compounds, can cause serious damage to reproductive health. These findings highlight the importance of developing and implementing preventive environmental health strategies. Policies should be designed to integrate ecological-reproductive risk management, particularly targeting rural communities that experience high exposure to household and agricultural chemicals.Methods : This cross-sectional epidemiological study involved 48 couples of reproductive age, selected using cluster-stratified sampling in rural agricultural areas. Data collection included structured interviews and household observations to assess exposure to common household chemicals such as floor cleaners, aerosol air fresheners, and pesticide residues.  Statistical analysis involved univariate and bivariate tests (Chi-square), as well as multivariate logistic regression, to determine independent relationships.Result: The prevalence of primary infertility was 35.4%. Bivariate analysis revealed significant associations between infertility and exposure to floor cleaners (p = 0.021), air fresheners (p = 0.034), and indoor pesticide residues (p = 0.015). Multivariate analysis confirmed indoor pesticide exposure (aOR = 3.92; 95% CI : 1.12–13.68) and air freshener use (aOR = 2.74; 95% CI : 1.01–9.15) as independent predictors of infertility.Conclusion: Exposure to household chemicals can cause serious damage to reproductive health. This risk increases when such exposure is combined with agricultural chemicals. These findings highlight the importance of developing and implementing preventive environmental health strategies. Policies should be designed to integrate ecological-reproductive risk management, particularly targeting rural communities that experience high exposure to household and agricultural chemicals.